The Role of Cognitive Metaphor in Chinese and Russian Languages - Xiuqing, Chen (Litera, 2023)
Communication refers to cognitive activity, therefore it is necessary to comprehensively investigate its individual aspects. The purpose of this article is to study the role of cognitive metaphor in Russian and Chinese. The subject of the study is cognitive metaphor in Russian and Chinese languages. The object of the study is the meaning of cognitive metaphor in Russian and Chinese. The author used methods of deduction and induction, comparative, contextual analysis. The author examines in detail the stages in the study of metaphor. Translation is a special act of retransmission in the form of international communication, in which the transfer of thoughts, feelings, and cultural experience is especially important. Through language it is possible to reflect the system of spiritual culture. The main content of the moral foundation of the Russian cultural tradition is the principles of Orthodoxy. Chinese traditions are based on a powerful moral experience, the basis of which are the ideas of Confucianism. The scientific novelty of the study consists in the analysis of specific examples of cognitive metaphors in the text materials of Chinese-Russian intercultural communication. The concept of metaphor is investigated, its characteristics in the cognitive approach are revealed. A metaphor is a universal sign that performs an epistemological function in the process of transmitting information. Cognitive metaphor allows you to know and describe the unknown through acquired experience, is a key element of the thought process. Cognitive metaphor is of great importance in economic and political international translations. Most concepts in the commercial sphere are multi-component and difficult to perceive. The specific examples of cognitive metaphors in the materials of Chinese-Russian intercultural communication are analyzed. Practical recommendations on the correct understanding and use of cognitive metaphors in the translation process are offered.